Effect of infant massage on growth of infants aged 1-5 months (Studies in BPS M.Susiyati Ledok Kulon village Bojonegoro Year 2013) - SUHARTIK, SUHARTIK (AKADEMI KESEHATAN RAJEKWESI BOJONEGORO, 2014)
Background : Growth problems in infants and toddlers is that the child will experience growth retardation since birth where the baby will be in the same median barriers will then experience growth the longer it will stay away from the median until the child is 18 months old. Infant massage is a touch stimulation that contains elements of love, attention, sound or speech, eye gaze, movements that can lead to increased appetite so as to sustain the growth of the baby . This study aims to prove the effect of infant massage on growth of infants aged 1-5 months. Methods : This study is a Quasi- Experiment with design with non equivalen control group design. The study population was recorded in all infants BPS M Susiyati Ledok Kulon village Bojonegoro in 2013. Data collection with pre-intervention, intervention and post-intervention. Data were analyzed with the Paired-samples T Test and independent-samples T Test.Results: The results showed that weight for age z scores proved significant treatment group ( p : 0.01) than the control group ( p : 0.07 ), length for age z scores significant treatment groups was significant (p : 0.01) than with the control group ( p : 0.06 ) , MUAC for age z scores significant treatment groups was significant (p : 0.04 ) compared with the control group ( p : 0.18 ), head circumference for age z scores significant treatment groups was significant (p : 0.03 ) compared with the control group ( p : 0.07 ).Conclusion : Infant massage effect on the treatment group compared to the control group where the treatment group experienced an increase in growth, while the control group experienced growth faltering . It is recommended to provide counseling to the community infant massage, infant growth monitoring using weight for age z score, length for age z scores, MUAC for age z scores, head circumference for age z scores.Keywords : infant massage, growth (weight for age z score, length for age z scores, MUAC for age z scores, head circumference for age z scores )